Faktor Risiko Diare pada Anak Usia 12-59 Bulan di Wilayah Kerja Puskesmas Kota Palembang Tahun 2025 - Farach Labita Anissa Putri; Esti Sri Ananingsih; Hendawati Hendawati; Faiza Yuniati; Ayu Febri Wulanda; Sherli Shobur (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diarrhea is a major cause of morbidity and mortality among children under five, particularly in developing countries such as Indonesia. The increasing prevalence of diarrhea is influenced by various factors, including low maternal knowledge, suboptimal Clean and Healthy Living Behavior (PHBS), and inadequate sanitation facilities, such as limited access to healthy latrines, wastewater disposal systems, and waste disposal facilities. This study aims to analyze the risk factors associated with the incidence of diarrhea in children aged 12–59 months in the working area of Puskesmas Pembina, Palembang City, in 2025. This research used an analytical observational design with a cross-sectional approach. A total of 107 respondents were selected using a purposive sampling technique. The results showed significant associations between maternal knowledge (p = 0.003), clean and healthy living behavior (p = 0.005), and the availability of healthy latrines (p = 0.000) with diarrhea incidence. However, no significant associations were found with wastewater disposal (p = 0.266) or waste disposal (p = 0.193). Maternal knowledge, PHBS, and ownership of healthy latrines are key factors in preventing diarrhea. Educational and sanitation improvement efforts are essential.